Tổng hợp, nghiên cứu cấu trúc và tính phát huỳnh quang của phức chất La(III) với 1,10-phenantrolin nitrat - Thành, Nguyễn Mậu; Vượng, Nguyễn Đức; Sỹ, Trần Đức (Vietnam Journal of Chemistry, 2014)
The complex components of La(III) with 1,10-phenantroline and nitrate ligands has been synthesized and identified by using thermal analysis and elemental analysis method. The structure of the complex was also confirmed by the modern analysis methods such as infrared (IR), Raman, 1H-NMR, 13C-NMR spectra. The molar ratio between the central ion and ligands has been studied and the obtained results showed that the highest performance is 292.5 nm.